The millennium development goals report 2008 (The United Nations, 2008)
The eight millennium development goals have been adopted by the international community as a framework for the development activities of over 190 countries in ten regions; they have been articulated into over 20targets and over 60indicators. This report summarizes progress towards the goals in each of the regions. However, any such synthesis inevitably masks the range and variety of development experiences in individual countries since the goals were adopted.